A comparative study of the political perceptions of rural and urban voters on the existence of a political dynasty in La Union - Apolinario, Charmaine C.; Jimenez, Paul M.; Zamoranos, Crissa P. (2003)
In the study"A Comparative Study on the Political Perceptions of Rural and Urban Voters on the Existence of a Political Dynasty in La Union", the researchers wanted to determine the similarities and differences on the political participation and perception of respondents from rural and urban barangays. Fifty(50) respondents from each barangay were randomly drawn from the Commission on Elections'(COMELEC) lists of registered voters. They were asked by the researchers to answer a set of questions about their general profile, voting profile, political participation and perception to be able to come up with an assessment of the present administration of the Ortega clan as a political dynasty. Perceived economic, political and social foundations of the political elites will be identified and evaluated to determine the degree of people's trust, support and loyalty to the political elites. Using uni-variate and bi-variate tables, the data gathered show that there were other factors that affect the people's degree of trust, support and loyalty to the political elites. Democratization was also found out to be low in both barangays because it came out in the data that people wanted to change the system but they do not or cannot initiate actions that would change the present administration -- Author's abstract.